A Comparative Analysis of the Accuracy of Crown Fabricated from Conventional Wax Patterns and CAD/CAM Technology – Milling and 3D Printing - MV Sunil Kumar; Rajesh Kumar; Ravindher Singh Saini; Rajesh Vyas; Sunil Kumar Vaddamanu (Journal of Pharmacy and Bioallied Sciences)
Background: Digital manufacturing techniques such as milling (subtractive) and 3D printing (additive) are increasingly used in dental restorations. These technologies promise enhanced precision and efficiency compared to traditional methods. However, the accuracy of marginal and internal fits of crowns produced by these techniques remains under-explored. Objective: To evaluate and compare the marginal and internal fit of dental crowns fabricated using two digital manufacturing techniques: Milling (subtractive) and 3D printing (additive). Materials and Methods: A maxillary first molar was replicated to create seven representative dies for each technique. Crowns were fabricated using both milling and 3D printing methods. The fit of the crowns was assessed using the silicone replica technique, measuring occlusal, axial, marginal gaps, and internal fit. Results: 3D printing demonstrated the most precise fit across all measurement points, with significantly smaller discrepancies compared to milling. The two-way ANOVA analysis confirmed a significant effect of the fabrication method on marginal and internal gaps, highlighting the superior performance of 3D printing. However, the silicone replica technique revealed fewer significant differences between the two methods. Conclusion: 3D printing offers enhanced precision and consistency in crown fabrication compared to milling. Despite promising results, further research is necessary to confirm the long-term efficacy and cost-effectiveness of these techniques. Future studies should focus on larger clinical cohorts to validate these findings.